A Monolithic Silicon Nanocrystal Photonic Transducer for a Real-time Biomarker Detection. (2016) - Huh, Chul; Lim, Jae Gab; Kim, Wan-Joong; Sim, Joo Yong; Kim, Bong-Kyu
Abstract: We demonstrate the monolithic Si nanocrystal (NC) photonic transducer for a real-time protein detection. The monolithic photonic transducer was composed of the Si NC light-emitting diode (LED), Si NC photodetector (PD), and Si nitride (SiNx ) optical waveguide that was optically self-aligned to the LED and PD. The Si NCs used as the fabrication of LED and PD were synthesized in the SiNx matrix. Antibodies were immobilized onto the surface of SiNx optical waveguide of the photonic transducer through self-assembled monolayers and surface aldehyde formation. Colloidal gold (Au) nanoparticles (NPs) were used to amplify the optical signal due to the strong surface plasmon resonance. The binding reaction of the Au NPs with the immobilized antibodies within the evanescent field at the transducer surface of the SiNx optical waveguide causes attenuated total reflection of the waveguided modes and thus reduction of the PD photocurrent. The detection limit of prostate-specific antigen (PSA) was around 1 ng/mL.